Primary Care Clinic Nurse Activities with a Telehealth Monitoring System. (January 2020) - Howland, Chelsea; Despins, Laurel; Sindt, Jeri; Wakefield, Bonnie; Mehr, David R.
The purpose of this study was to evaluate differences in the types of nursing activities and communication processes reported in a primary care clinic between patients who used a home-based monitoring system to electronically communicate self-monitored blood glucose and blood pressure values and those who assumed usual care. Data were extracted from electronic medical records from individuals who participated in a randomized controlled trial comparing in-home monitoring and usual care in patients with Type 2 diabetes and hypertension being treated in a primary care clinic. Data about nursing activities initiated by primary care clinic nurses were compared between groups using descriptive statistics and independent t -tests. Significant differences between groups were identified for the direct care nursing activities of providing lifestyle and health education, medication adjustments, and patient follow-up. This study provides evidence of greater nursing activity reported in a primary care clinic in patients who utilized a home-based monitoring system.